Barriers to Food Stamps in New York State: A Perspective from the Field. - Kaye, Lara; Lee, Eunju; Chen, Yi Yi (Journal of Poverty)
Although the Food Stamp Program provides nutritional assistance to families and individuals in need, barriers to access, eligibility, and receipt of food stamp benefits do exist. Minimizing and potentially eradicating significant barriers requires a better understanding of which barriers are the most prevalent and persistent and a plan for addressing them. Using data from 73 community based organizations in New York State over a 4-year time period, the authors identify barriers that are most frequently mentioned and do not abate over time. A number of recommendations are presented to address barriers in general and the specific barriers that were identified.